THE IMPORTANCE OF DIGITALIZATION IN DRIVING INNOVATION, STRATEGY, AND COMPETITIVE ADVANTAGE FOR MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES)IN BANJARMASIN - Diana Hayati; Rizki Amalia Afriana; Ruslinda Agustina; Rara Gustiana (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Digitalization has become a crucial catalyst for business transformation in the digital economy era, including for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This research aims to analyze the role of digitalization in encouraging innovation, developing effective business strategies, and achieving competitive advantages for micro and small enterprises (MSMEs). Through a qualitative approach involving literature studies and in-depth interviews with MSME actors across various sectors, it was found that the adoption of digital technologies, such as e-commerce, social media, and digital management systems, can increase operational efficiency, expand market reach and accelerate the process of product and service innovation. However, the study's results also reveal that significant challenges persist, including limited access to technology, low digital literacy, and a lack of employee skills in MSMEs. Therefore, synergy between the government, industry players, and education and training institutions is needed to create an inclusive and sustainable digital ecosystem for MSMEs. In conclusion, digitalization is not only a tool but also a strategic foundation for enhancing the competitiveness of MSMEs in the face of increasingly dynamic global competition.